Racial disparity in HbA1c persists when fructosamine is used as a surrogate for mean blood glucose in youth with type 1 diabetes. Issue 7 (21st August 2018) - Chalew, Stuart; Hamdan, Mahmoud
Abstract : Background: Blacks have been reported to have higher hemoglobin A1c (HbA1c) than Whites even after adjustment for differences in blood glucose levels. Potentially glucose‐independent racial disparity in HbA1c is an artifact of glucose ascertainment methods. In order to test this possibility, we examined the relationship of HbA1c with race after adjustment for concurrent fructosamine level as a surrogate for mean blood glucose (MBG). Methods: Youth with type 1 diabetes self‐identified as either Black or White had blood drawn for HbA1c, fructosamine complete blood count, ferritin, and soluble transferrin receptor (sTfR) at a clinic visit. MBG was calculated as the average of self‐monitored capillary glucoses over the preceding 30 days. The effect of race on HbA1c was evaluated in a general linear model adjusting for either MBG or fructosamine, along with other covariates. Results: Fructosamine was correlated with both HbA1c ( r = 0.73, P < .0001), MBG ( r = 0.46, P < .0001), red cell distribution width coefficient of variation (RDW‐CV) ( r = 0.31, P = .0045), Fe ( r = 0.27, P = .017), and sTfR ( r = 0.32, P = .0042). HbA1c was approximately 0.7% higher in Blacks than Whites after adjustment for fructosamine along with age, gender, RDW‐CV, Fe, sTfR. Conclusions: Blacks tend to have higher HbA1c than Whites even after statistical adjustment for fructosamine levels as a surrogate for MBG. Thus, HbA1c tends to overestimate corresponding MBG or fructosamine levels in Black patients. Racial differences should be taken into consideration when using HbA1c as a guide to diagnosis and therapy of diabetes in mixed‐race populations.